The Apprenticeship Framework in England: a new beginning or a continuing sham? - Brockmann, Michaela [Verfasser]; Clarke, Linda [Verfasser]; Winch, Christopher [Verfasser] (My University, 2010)
"This paper highlights critical shortcomings in the approach to apprenticeship in England and argues that the proposed Apprenticeship Framework is unlikely to fulfil its stated aims of enhancing quality and quantity. The key weaknesses identified are a clear definition of what constitutes an apprenticeship framework, an educational component, employee involvement and lack of recognition of alternative college-based routes. Drawing on a recent cross-national study, the authors compare the English situation with the vocational education and training systems of other leading European countries. These embody a distinctly different approach and framework, being based on social partnership and the education of young people into a broadly defined occupation. It is shown how the current proposals mark a potential step backwards and a departure from the principles of the 1944 Education Act by ignoring general and civic educational elements in young people's formation. Above all, for any framework to be successful, it needs to take into account the longer term interests of employees, given changes in the labour market, and to address the issue of employer disengagement. The conclusions drawn suggest ways forward." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.1.1 Ausbildungsstellenmarkt; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2.1 Westeuropa; Berufsausbildung; Ausbildungsplatzdefizit; Nationaler Qualifikationsrahmen; Lernen am Arbeitsplatz; Beziehung Bildungssystem Beschäftigungssystem; England